The Permeability of Waste Fiber Recycled Concrete - Jinghai ZHOU; Tianbei KANG; Fengchi WANG (Medžiagotyra, 2019)
Permeability is one of the major performances for recycled aggregate concrete, which affects the durability and service life of concrete structures. In most cases, the main factor affecting the permeability of recycled aggregate concrete is the pore structure. Considering water-cement ratio, replacement rate of recycled aggregates, waste fiber length, and volume fraction of waste fibers as the design variables, pore structure and gas permeability were studied experimentally. In addition, fractal theory was here used to assess the pore structure of waste fiber recycled concrete and study the effects of pore structure on permeability. The results showed that the pore size distribution had a small impact on the permeability with the water-cement ratio and replacement rate of recycled aggregates increasing. The fractal dimension can be used to describe the complexity of the pore structure quantitatively. There is an obvious linear relationship between fractal dimension and gas permeability. The larger the pore volume fractal dimension, the better the impermeability of waste fiber recycled concrete.